A novel outbreak enterovirus D68 strain associated with acute flaccid myelitis cases in the USA (2012–14): a retrospective cohort study. Issue 6 (June 2015) - Greninger, Alexander L; Naccache, Samia N; Messacar, Kevin; Clayton, Anna; Yu, Guixia; Somasekar, Sneha; Federman, Scot; Stryke, Doug; Anderson, Christopher; Yagi, Shigeo; Messenger, Sharon; Wadford, Debra; et al.
Summary Background Enterovirus D68 was implicated in a widespread outbreak of severe respiratory illness across the USA in 2014 and has also been reported sporadically in patients with acute flaccid myelitis. We aimed to investigate the association between enterovirus D68 infection and acute flaccid myelitis during the 2014 enterovirus D68 respiratory outbreak in the USA. Methods Patients with acute flaccid myelitis who presented to two hospitals in Colorado and California, USA, between Nov 24, 2013, and Oct 11, 2014, were included in the study. Additional cases identified from Jan 1, 2012, to Oct 4, 2014, via statewide surveillance were provided by the California Department of Public Health. We investigated the cause of these cases by metagenomic next-generation sequencing, viral genome recovery, and enterovirus D68 phylogenetic analysis. We compared patients with acute flaccid myelitis who were positive for enterovirus D68 with those with acute flaccid myelitis but negative for enterovirus D68 using the two-tailed Fisher's exact test, two-sample unpaired t test, and Mann-Whitney U test. Findings 48 patients were included: 25 with acute flaccid myelitis, two with enterovirus-associated encephalitis, five with enterovirus-D68-associated upper respiratory illness, and 16 with aseptic meningitis or encephalitis who tested positive for enterovirus. Enterovirus D68 was detected in respiratory secretions from seven (64%) of 11 patients comprising two temporally and geographically linked acute flaccid myelitis clusters at the height of the 2014 outbreak, and from 12 (48%) of 25 patients with acute flaccid myelitis overall. Phylogenetic analysis revealed that all enterovirus D68 sequences associated with acute flaccid myelitis grouped into a clade B1 strain that emerged in 2010. Of six coding polymorphisms in the clade B1 enterovirus D68 polyprotein, five were present in neuropathogenic poliovirus or enterovirus D70, or both. One child with acute flaccid myelitis and a sibling with only upper respiratory illness were both infected by identical enterovirus D68 strains. Enterovirus D68 viraemia was identified in a child experiencing acute neurological progression of his paralytic illness. Deep metagenomic sequencing of cerebrospinal fluid from 14 patients with acute flaccid myelitis did not reveal evidence of an alternative infectious cause to enterovirus D68. Interpretation These findings strengthen the putative association between enterovirus D68 and acute flaccid myelitis and the contention that acute flaccid myelitis is a rare yet severe clinical manifestation of enterovirus D68 infection in susceptible hosts. Funding National Institutes of Health, University of California, Abbott Laboratories, and the Centers for Disease Control and Prevention.